2021
DOI: 10.1002/pmic.202000129
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis reveals altered enzyme expression profile in Zea mays roots during the early stages of colonization by Herbaspirillum seropedicae

Abstract: The use of plant growth-promoting bacteria as agricultural inoculants of plants should be encouraged because of their prominent role in biological nitrogen fixation, the increase of nutrient uptake by roots, abiotic stress mitigation, and disease control. The complex mechanisms underlying the association between plant and beneficial bacteria have been increasingly studied, and proteomic tools can expand our perception regarding the fundamental molecular processes modulated by the interaction. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The diazotrophic bacterium H. seropedicae, can affect the nitrogen metabolism of the plant host [ 25 , 26 , 48 , 49 , 50 ]. Using transcriptomic and proteomic approaches, this study allowed us to better understand how inoculation can modulate nitrogen acquisition and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The diazotrophic bacterium H. seropedicae, can affect the nitrogen metabolism of the plant host [ 25 , 26 , 48 , 49 , 50 ]. Using transcriptomic and proteomic approaches, this study allowed us to better understand how inoculation can modulate nitrogen acquisition and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diazotrophic bacteria can upregulate important genes involved in nitrogen metabolism such as NR , NiR , and GS , which encode nitrate reductase, nitrite reductase, and glutamine synthetase, respectively, and collectively increase the activity of these enzymes in plants [ 11 , 21 , 76 , 77 , 78 , 79 ]. As illustrated in Figure 2 , the modulation of nitrogen metabolism results in higher N storage in the vacuole compartment, leading to better plant growth and development.…”
Section: Molecular Mechanisms Involved In the Association Of Plant An...mentioning
confidence: 99%
“…These endophytic and associative diazotrophic bacteria are considered plant growth–promoting rhizobacteria (PGPR), as they improve plant performance by enhancing the availability of nutrients and improve soil fertility, mainly through BNF and phosphate solubilization [ 17 , 18 , 19 ]. In addition, they produce plant growth regulators and are involved in the modulation of phytohormone and defense responses [ 20 , 21 , 22 ], production of antioxidants, osmotic adjustment, and plant tolerance against biotic and abiotic stresses [ 23 , 24 ]. A large number of important crops in agriculture are non-nodulating grasses, such as maize, rice, wheat, sorghum, and sugarcane, showing the importance of studies and production of bioinoculant non-nodulating diazotrophic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al [ 22 ] concluded that maize plants inoculated with Herbaspirillum seropedicae showed higher vegetative development under low N availability in the soil. These effects are related to biological nitrogen fixation (BNF) [ 23 ], modulation of enzymes in response to different types of stress [ 15 , 24 ], and/or bioprotection and mitigation of water stress [ [25] , [26] , [27] , [28] ] promoted by Herbaspirillum seropedicae.…”
Section: Introductionmentioning
confidence: 99%